KONTEKSTUALISASI TEOLOGI KEADILAN DALAM HUKUM QISHASH DAN POLIGAMI - Ismail Keri; Dr. Misbahuddin; Dr. Wahid Haddade (IAIN BONE, 2022)
This article discusses the theology of Islamic legal justice, in Qishash and Polygamy. Justice theology is a discourse that discusses justice based on religious reasoning. This article is a literature review with a normative theological approach. In the discussion it was stated that: Justice is absolute and morally binding, therefore believers are warned not to let hatred against someone cause them to violate the boundaries of justice, or make themselves deviate from the ideal of justice, because justice is very close to piety. and truth. The terminology of justice in Islamic law is interpreted as: fair in the sense of being similar or impartial and impartial, justice also means conformity and balance. In addition, justice also means paying attention to individual rights and giving these rights to their owners. (puts everything in its place).